Highly responsive CO2 detection by an improved & compact gas sensor using mid-IR spectroscopy - Mohd Rashidi, Salim; Mohd Haniff, Ibrahim; Asrul Izam, Azmi; Muhammad Yusof, Mohd Noor; Ahmad Sharmi, Abdullah; Nor Hafizah, Ngajikin; Hadi, Manap; Dooly, Gerard; Lewis, Elfed (UTeM, 2018)
An improved and compact gas sensor using mid-infrared spectroscopy for highly responsive Carbon Dioxide (CO2) detection is presented. The sensing principle is based on open-path direct absorption spectroscopy in the mid-infrared region. The improved reflective structure of optical gas sensor consists of low cost and compact components. Several gas cell configuration which includes SISO, 2-MISO, 4-MISO and 8- MISO were simulated using ZEMAX®12 using non-sequential ray tracing technique to get the optimum radius of the reflective curved surface. Sensitivity analysis has shown that the optimised structure of 4-MISO yields the highest sensitivity and power efficiency of -0.2895%-1 and 12.298% respectively. The developed gas sensing system using the optimised gas cell has shown the capability of accurately detecting CO2 concentration between 1.5% and 5.8% with no cross-sensitivity with other gases present in the gas cell. The newly developed CO2 sensor exhibits high responsivity with the recorded rise time and fall time of less than 1 second respectively.